1994
DOI: 10.1017/s030822960002568x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive performance of pigs selected for components of efficient lean growth

Abstract: This study determined the correlated responses in reproductive performance after five generations of divergent selection for components of efficient lean growth rate in Large White pigs.Data were collected from five generations of pigs divergently selected for daily food intake (DFI), lean food conversion (LFC), lean growth rate on ad-libitum feeding (LGA) and lean growth rate on restricted or scale feeding (LGS). In each selection group, there were high, low and control lines, each consisting of 10 boars and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
54
6
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 0 publications
7
54
6
2
Order By: Relevance
“…The values of PPBD in high-per- forming herds would be feasible targets for commercial herds. Our results are consistent with previous studies reporting that the parity 1 sows with a high percentage of stillborn piglets have a low number of total pigs born [2,10]. Higher PPBD in parity 1 sows than parity 2 and 3 sows can be partially explained by a gilt's first experience of parturition and a difficult farrowing due to a narrow birth canal [17].…”
Section: Discussionsupporting
confidence: 92%
“…The values of PPBD in high-per- forming herds would be feasible targets for commercial herds. Our results are consistent with previous studies reporting that the parity 1 sows with a high percentage of stillborn piglets have a low number of total pigs born [2,10]. Higher PPBD in parity 1 sows than parity 2 and 3 sows can be partially explained by a gilt's first experience of parturition and a difficult farrowing due to a narrow birth canal [17].…”
Section: Discussionsupporting
confidence: 92%
“…Genetic improvement of piglet survival by selection based on birth weight does not seem to be a viable alternative Several studies (Kerr and Cameron, 1995;Roehe and Kalm, 2000) reported that the piglet's individual birth weight was the most important factor affecting pre-weaning mortality. Because of the low heritability of piglet survival and relatively high heritability for BW, the authors suggested selection for increased birth weight to improve survival, rather than direct selection for piglet survival.…”
Section: Discussionmentioning
confidence: 99%
“…Kerr and Cameron, 1995;Roehe and Kalm, 2000) have shown that the piglet's individual birth weight was the most important factor determining pre-weaning mortality. It brings out a hypothesis that selection for higher individual birth weight could be a good alternative to improve survival rate.…”
Section: Introductionmentioning
confidence: 99%
“…Selection for litter size has increased the resource demanding processes of pregnancy and lactation, whereas selection for fast lean growth may have indirectly put an increased demand on delivery of nutrients by the placenta and may have put conceptuses at a greater risk of prenatal mortality (Vallet et al, 2002) and stillbirth (Grandinson et al, 2005). Selection for increased lean growth has resulted in higher prenatal mortality in several experiments (Vangen, 1972;Kerr and Cameron, 1995). Since animals from both genetic groups were fed the same diet according to the same norm during gestation, G98 sows may have been restricted in their ability to provide enough nutrients to their foetuses in late gestation.…”
Section: Discussionmentioning
confidence: 99%